The Impact of Inclusive Leadership and Job Satisfaction on Employee Performance: The Mediating Role of Affective Commitment at Perum Bulog Aceh Regional Office (International Journal of Scientific Research and Management (IJSRM), 2025)
The purpose of this study is to determine the extent to which inclusive leadership and job satisfaction influence employee performance, with affective commitment serving as a mediating factor, among employees of Perum Bulog Kanwil Aceh. This research employs a quantitative methodology. The sample consists of all 141 employees of Perum Bulog Kanwil Aceh. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results indicate that inclusive leadership has a positive and significant effect on affective commitment at the Bulog Regional Office of Aceh. Conversely, job satisfaction does not have a significant impact on employees’ affective commitment at the same office. Inclusive leadership does not significantly influence employee performance at the Bulog Regional Office of Aceh. However, job satisfaction has a positive and significant effect on employee performance. Affective commitment also positively and significantly affects employee performance. Furthermore, inclusive leadership significantly influences employee performance through the mediating role of affective commitment. Similarly, job satisfaction significantly affects employee performance via affective commitment mediation at the Bulog Regional Office of Aceh